Knowledge, attitudes and practices towards emergency contraceptive pill use among women of reproductive age in Lira District, Northern Uganda: A cross-sectional study - Josephine Vanessa Nakalema; Marvin Musinguzi; Deo Benyumiza; Eustes Kigongo; Edward Kumakech; Rashida Namuwaya; Joshua Oryem Opido; Nicholas Damulira; Raymond Tumwesigye; Amir Kabunga; Marc Sam Opollo (PLoS ONE, 2026)
Background Emergency contraceptives (ECs) are used to prevent unintended pregnancy after unprotected sexual intercourse. In Uganda, unsafe abortion remains a major contributor to maternal mortality, particularly in resource-limited settings such as Northern Uganda. Greater use of emergency contraceptive pills could help reduce unintended pregnancies and their related consequences. However, information on women’s knowledge, attitudes, and practices regarding emergency contraceptives remains limited. This study therefore assessed the knowledge, attitudes, and practices of women of reproductive age towards emergency contraceptives in Lira District. Method This was a community-based cross-sectional study conducted between June and July 2023. A total sample size of 600 was estimated; however, 585 respondents were ultimately selected using multi-stage cluster sampling. Data were analyzed using SPSS version 26 at the univariate, bivariate, and multivariate levels. Results The study had a response rate of 97.5% (585). Emergency contraceptive pill usage was at 30.6%. The mean age of participants was 28.01 ± 7.6 years. Majority of the respondents 374 (63.93%) had good knowledge about emergency contraceptive pills. Most of the respondents 386 (65.98%) had negative attitudes towards emergency contraceptive pills. The factors associated with use of emergency contraceptive pills include: having poor knowledge about emergency contraception (AOR = 0.11, 95% CI 0.07–0.21, p < 0.001), having positive attitudes towards emergency contraceptive pills (AOR = 3.89, 95% CI 2.59–5.84, p < 0.001), and being unmarried (AOR = 2.85, 95% CI 1.83–4.43, p < 0.001). Conclusion Emergency contraceptive pill utilization among women of reproductive age in Lira District was modest, with about three in ten women reporting use in the previous month. Utilization was significantly influenced by knowledge, attitudes, and marital status. These findings highlight the need for interventions that strengthen knowledge, address negative attitudes, and support appropriate use of emergency contraception.